Risk assessment at open dumping area using Monte Carlo simulation - Mohd Pauzi N.I.; Razali Z.C. (Institute of Physics Publishing, 2023)
Bearing capacity; Geotechnical engineering; Groundwater; Groundwater pollution; Hazards; Intelligent systems; Risk assessment; Tropical engineering; Direct shear box test; Dumping site; Hazardous gas; Potential hazards; Potential risks; Sieve analysis; Soil sample; Waste soils; Monte Carlo methods